Problematic online gaming, subjective health complaints, and depression among adolescent gamers from the United States: the role of console-gaming aggression. Issue 3 (3rd July 2022) - Wright, Michelle F.; Wachs, Sebastian
ABSTRACT: The purpose of this study was to examine the longitudinal relationship between problematic online gaming and subjective health complaints and depressive symptoms, and the moderation of console-gaming aggression (i.e. verbal aggression, camping, trolling) in this relationship. Participants were 202 adolescents (86% boys; M age = 12.99 years) in the 7 th or 8 th grade who played first-person shooter games. They completed questionnaires on problematic online gaming, console-gaming aggression, subjective health complaints, and depressive symptoms. Six months later (Time 2), they completed questionnaires on subjective health complaints and depressive symptoms again. Findings revealed that problematic online gaming and console-gaming aggression were positive predictors of Time 2 subjective health complaints and depressive symptoms, while controlling for Time 1 levels and gender. Moderating effects were found as well, indicating that high levels of console-gaming aggression increased the positive relationship between problematic online gaming and depressive symptoms. These effects were also replicated for verbal aggression, problematic online gaming, and subjective health complaints. These findings suggest the importance of considering the implications of console-gaming aggression and problematic online gaming for the physical and mental health of adolescents. Impact Summary: Prior State of Knowledge : Problematic online gaming and aggressive behaviors are linked to negative outcomes, including depression and subjective health complaints. Longitudinal research further supports this connection for depression, but not for subjective health complaints or various types of aggression via console games. Novel Contributions : Few studies have focused on various types of aggression and the longitudinal associations among problematic online gaming, depression, and subjective health complaints, while controlling for previous levels of depression and subjective health complaints. The present research addresses these gaps. Practical Implications : Findings of the present research has implications for clinicians and researchers concerned with identifying adolescents who might be at risk for negative outcomes.